Implementation of local superior plant of forest and land rehabilitation based on community perception in Girimulyo Village, East Lampung Regency, Indonesia - Rhezandhy Gunawan; Indra Gumay Febryano; Idi Bantara; Slamet Budi Yuwono; Christine Wulandari; Hari Kaskoyo; Samsul Bakri; Rahmat Safe'i (Talenta Publisher, 2024)
Public perception is important in implementing Forest and Land Rehabilitation (FLR) in forest areas where tenure conflicts are thick. The research aims to analyze community perceptions of the implementation of FLR based on local superior plants in Girimulyo Village, Marga Sekampung District, East Lampung Regency. Data collection was carried out using a questionnaire of 30 respondents determined by purposive sampling. The collected data was analyzed descriptively to analyze farmers' perceptions and their relationship to social, economic and ecological aspects. Public perception of FLR activities based on forestry plants (Trees) is included in the medium category. The public's perception of FLR based on the superior Siger avocado crop in terms of social, economic and ecological aspects is in the high category. The community realizes that FLR for local superior plants is more profitable than FLR based on forestry plants. It is necessary to increase human resources in the Mulyo Lestari Agro Forest Farmers Group in order to facilitate the administrative management process